Mental Processes of the Main Character in Jhumpa Lahiri’s Interpreter of Maladies - Isti’anah, Arina (Language Circle: Journal of Language and Literature, 2018)
The study of main characters becomes one of delicate angles to observe in literary work. Instead of the various literary criticisms, linguistics also provides stylistics as the approach to appreciate and interpret literary work, including character analysis. ―Interpreter of Maladies‖ is one of the short stories written by Jhumpa Lahiri which attracts readers‘ attention. Readers may comment the way Lahiri portrays the main character of the story, Mr. Kapasi. To interpret the character‘s feeling in the story, Halliday‘s Functional Linguistics is employed to observe what happens in the character‘s thought. The previous purpose is facilitated by transitivity analysis focusing on the mental process analysis. Transitivity focuses on the clause analysis as the unit which brings meanings, including types of participants in the clause. Halliday divides mental process into four: perceptive, cognitive, emotive, and desiderative. The analysis shows that perceptive, cognitive, and affective dominate the narrator‘s description on Mr. Kapasi, while desiderative appears the least in the main character. The choice of those mental process types signals that Lahiri portrays Mr. Kapasi as an attentive, intellectual, and affectionate character.